PENGATURAN AIR DAN NUTRISI SECARA OTOMATIS PADA TANAMAN HIDROPONIK BERBASIS ARDUINO - Nugraha, Hasbi Fardian; Rasmana, Susijanto Tri; Puspasari, Ira (Journal of Control and Network Systems (JCONES), 2017)
Hydroponics is one method of farming without using soil in the planting media, but can produces better than soil in general because the result of farm would be more clean and practical. The community usually use this cropping manner for agriculture with a narrow land. Hydroponics now widely used community because it proved profitable and generate maximum agricultural production. In this final task was created the way take care of hydroponics automatically. The design of electronic instrument using the Arduino Mega microcontroller that obtain input from sensors used, and will be processed by an Arduino Mega microcontroller using the setting clean water and nutrient water method automatically. The systems designed have been able to to reduce waste of time as well as the performance of the user itself. By simply setting up the water in the backup container, set up water nutrients, and chose nutrients options with the keypad. The tool has been able to do the automation of water charging and nutrients mixing automatically. So tool is able to improve efficiency and effectiveness in the use of nutrients daily. Based on the test results indicate the level of success of this tool in determining the success rate of 100% correctly, and the error rate of this instrument of 0%.Keywords: Arduino Mega, Hydroponics, Water Management.